Paradigm Shift in Legal Protection of Health Workers Before and After the 2023 Health Law: A Comparative Review - M. Yadi Mahendra Muhyin; Asep Sapsudin (Research Horizon, 2026)
Law Number 17 of 2023 strengthens legal protection for medical personnel and healthcare workers through an omnibus approach, addressing prior regulatory fragmentation and unclear distinctions between medical risk and negligence that led to legal uncertainty, criminalization risks, and defensive medicine that undermined service quality and efficiency. This study analyzes differences in the construction of legal protection before Law Number 17 of 2023 on Health, examines the implications of the paradigm shift in medical dispute resolution toward legal certainty and substantive justice, and formulates policy recommendations to strengthen a more just and proportionate national health law ecosystem. This normative legal research uses statutory, comparative, and conceptual approaches with qualitative-prescriptive analysis, based on Radbruch, Friedman, and Pound theories. The findings show that Law Number 17 of 2023 shifts the punitive model into a restorative model by strengthening protection based on professional standards, disciplinary board recommendations as an initial filter, and prioritization of dispute resolution through alternative mechanisms outside the court system. Therefore, the law in question provides a clearer, hierarchical legal foundation to protect healthcare workers. However, its effectiveness depends on harmonized implementing regulations, institutional strengthening, and balanced protection between healthcare workers’ legal safeguards and patients’ right to remedies.